Prevalence of peritonitis and mortality in patients with ESKD treated with chronic peritoneal dialysis in Africa: a systematic review - Jean Jacques Noubiap (BMJ Publishing Group, 2020)
Objective The aim of this study was to report the prevalence of peritonitis and mortality in patients with end-stage kidney disease (ESKD) treated with chronic peritoneal dialysis (PD) in Africa.Design Systematic review.Setting Africa.Participants Patients with ESKD in Africa.Interventions PD in its varied forms.Primary and secondary outcomes PD-related peritonitis rate (primary outcome), time-to-discontinuation of PD, mortality.Data sources Four databases, including PubMed, Embase, Web of Science and Africa Journal Online were systematically searched from 1 January 1980 to 31 December 2019.Eligibility criteria Studies conducted in Africa reporting peritonitis rate and mortality in patients treated with PD.Data extraction and synthesis Two reviewers extracted and synthesised the data using Microsoft Excel. The quality of included data was also assessed.Results We included 17 studies from seven African countries representing 1894 patients treated with PD. The overall median age was 41.4 years (IQR: 38.2–44.7) with a median time on PD of 18.0 months (17.0–22.6). An overall median peritonitis rate of 0.75 (0.56–2.20) episodes per patient-year (PPY) was observed and had declined with time; peritonitis rate was higher in paediatric studies than adult studies (1.78 (1.26–2.25) vs 0.63 (0.55–1.87) episodes PPY). The overall median proportion of deaths was 21.1% (16.2–25.8). Culture negative peritonitis was common in paediatric studies and studies that reported combined outcomes of continuous ambulatory PD and automated PD. Both 1-year and 2-year technique survival were low in all studies (83.6% and 53.0%, respectively) and were responsible for a high proportion of modality switch.Conclusions Our study identifies that there is still high but declining peritonitis rates as well as low technique and patient survival in PD studies conducted in Africa. Sustained efforts should continue to mitigate factors associated with peritonitis in patients with ESKD treated with PD in Africa.PROSPERO registration number CRD42017072966.